Specific features of the development of Rhopalosiphum padi in connection with migration and transfer of the viral infection to host and non-host plants using potato as an example - Elena S Gandrabur; ALLA B. VERESHCHAGINA (Society for Indonesian Biodiversity, 2019)
Abstract. Gandarabur ES, Vereshchagina AB. 2019. Specific features of the development of the bird cherry-oat aphid Rhopalosiphum padi (L.) in connection with migration and transfer of the viral infection to host and non-host plants using potato as an example. Biodiversitas 20: 3439-3447. Using Rhopalosiphum padi (L.), which lives in the North-West of the Russian Federation, as an example, the long-term data on the timing of its spring migration from bird cherry to herbaceous plants are summarized and their analysis, related to the wing formation in aphid colonies and the accompanying weather conditions, is given. It was found out, those peculiarities of behavior of spring emigrants of Rh. padi during the host selection depend on the motivation for a long-distance flight, include repeated take-off and testing and may be accompanied by visits to the non-host plants during 4 days. Migration and settling behavior of aphids underlie their ability to transfer non-persistent viruses to host and non-host plants. The obtained data allow adjusting the methods of plant protection including the viral infection.